Air Pollution and Primary DNA Damage among Zagreb (Croatia) Residents: A Cross-Sectional Study - Marko Gerić; Gordana Pehnec; Katarina Matković; Jasmina Rinkovec; Ivana Jakovljević; Ranka Godec; Silva Žužul; Ivan Bešlić; Ante Cvitković; Luka Delić; Pascal Wild; Irina Guseva Canu; et al. (MDPI AG, 2024)
More than eight million premature deaths annually can be attributed to air pollution, with 99% of the world's population residing in areas below recommended air quality standards. Hence, the present study aimed to examine the association between primary DNA damage and air pollution data among 123 participants enrolled between 2011 and 2015 in Zagreb, Croatia. While most measured air pollutants adhered to regulatory limits, benzo[a]pyrene concentrations bound to PM10 exceeded them. Factorial analysis narrowed down air pollution data to four exposure factors (particulate matter, two metal factors, and other pollutants). Despite the absence of significant positive associations between modeled air pollution exposure factors and comet assay descriptors (tail length, tail intensity, tail moment, and highly damaged nuclei), the critical health implications of air pollution warrant further investigations, particularly with biomarkers of exposure and different biomarkers of effect in populations facing air pollution exposure.